Controllable NO emission and high flame performance of ammonia combustion assisted by non-equilibrium plasma. (1st July 2022) - Lin, Qifu; Jiang, Yiman; Liu, Chengzhou; Chen, Longwei; Zhang, Wenjin; Ding, Jun; Li, Jiangang
Highlights: An ammonia combustion device using gliding arc plasma (GAR) reactor was proposed. GAP reactor combined with swirl burner enhances combustion and reduces NO emission. Air GAP and ammonia injected from burner swirl ring promoted ammonia combustion. Ammonia GAP and air injected from swirl ring yielded NO emissions below 100 ppm with ammonia flow rate of 10 SLM. Abstract: Owing to the high NOx emission and low combustion performance of ammonia fuel, many researchers are exploring new methods for enhancing ammonia combustion performance without the need for blending with other hydrocarbon fuels. In this study, a gliding arc plasma (GAP) reactor was combined with a swirl burner to simultaneously enhance combustion performance and reduce NO emission. The effects of the gas discharge medium, equivalence ratio (φ), and gas flow rate on flame stability, flame speed, and NO emission were investigated. Experimental results show that with air GAP and ammonia injected from the swirl ring of the burner, the optical emission spectrum of the ammonia flame was dominated by the atomic spectrum of O*, Hβ, and the molecular spectrum of the NH* and OH* components, which significantly promoted ammonia combustion performance, including combustion limitation and NO emission. In addition, with an NH3 gas flow rate of 10 SLM, optimal NO emission was reduced to approximately 100 ppm, even though the equivalence ratio φ was in a lean flame, and near zero at an equivalence ratio φ larger than 1.6. With ammonia GAP and the air injected from the swirl ring of the swirl burner, online hydrogen from ammonia decomposition was produced by ammonia GAP, and NO emission was always less than 100 ppm for various equivalence ratios φ with an NH3 gas flow rate of 10 SLM. These results could be used for ammonia combustion with low NO emission, which could be applied to the ammonia fuel industry.